Analisis Literasi Keuangan dan Akses Modal terhadap Kinerja Keuangan Pelaku UMKM di Kabupaten Subang - Kartini, Titin; Wijaya, John Henry (https://jurnal.binamandiri.ac.id/, 2024)
The MSME sector serves as a crucial pillar of the national economy. Despite facing various challenges in recent years that have affected its performance and growth, MSMEs have demonstrated a strong ability to recover and adapt to dynamic economic conditions. This study aims to analyze the impact of financial literacy and access to capital on the financial performance of MSMEs in Subang Regency. The case study explores the relationship between financial literacy and access to capital, with a particular focus on the influence of capital access. The research method includes surveys and analysis of primary data collected through questionnaires from MSME operators in Subang Regency. Statistical analysis reveals that among the two factors studied, only access to capital significantly influences the financial performance of MSMEs. These findings provide crucial insights for stakeholders involved in policy and support for MSME development in Subang Regency. By emphasizing the importance of adequate access to capital, whether through formal financial institutions or government support programs, it is expected that MSME financial performance and sustainability can be enhanced. The study also highlights the need to improve financial literacy among MSME operators as part of a comprehensive strategy to strengthen this sector.